2008
DOI: 10.1029/2007jd009598
|View full text |Cite
|
Sign up to set email alerts
|

Total lightning activity as an indicator of updraft characteristics

Abstract: [1] This study investigates the relationship of total lightning activity and updraft characteristics, such as updraft volume and maximum updraft speed, for a number of storms of different types occurring in the High Plains and in Northern Alabama. Ground-based Doppler and dual polarimetric radar observations were used to compute updraft characteristics. Also, ground-based total lightning data were available at both locations. Results show that time series of updraft volume in the charging zone (at temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
252
5
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(281 citation statements)
references
References 42 publications
(76 reference statements)
20
252
5
4
Order By: Relevance
“…Multiple studies have confirmed and elaborated on the relationship between lightning activity and multi-Doppler radar derived updrafts (Lang and Rutledge 2002;Tessendorf et al 2007b,a;Deierling and Petersen 2008;Calhoun et al 2013) and several have investigated the relationships between polarimetric variables and electrical activity in deep convection storms (Carey and Rutledge 1998;Tessendorf et al 2005;Wiens et al 2005;Bruning et al 2007;Lund et al 2009;Payne et al 2010;Griffin et al 2014). (Heistermann et al 2015).…”
Section: B Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have confirmed and elaborated on the relationship between lightning activity and multi-Doppler radar derived updrafts (Lang and Rutledge 2002;Tessendorf et al 2007b,a;Deierling and Petersen 2008;Calhoun et al 2013) and several have investigated the relationships between polarimetric variables and electrical activity in deep convection storms (Carey and Rutledge 1998;Tessendorf et al 2005;Wiens et al 2005;Bruning et al 2007;Lund et al 2009;Payne et al 2010;Griffin et al 2014). (Heistermann et al 2015).…”
Section: B Backgroundmentioning
confidence: 99%
“…Graupel is produced in regions where riming growth is dominant, in other words, regions of deep convection updrafts. Studies, for example, Deierling and Petersen (2008) have confirmed a strong link between updraft volume and total flash rate in storm systems, with Wiens et al (2005) stressing the importance of using flash density, rather than raw VHF source density, as a measure of lightning activity.…”
Section: B Backgroundmentioning
confidence: 99%
“…These large volumes of moderate-to-large reflectivities above the freezing level suggest that frozen precipitation (particularly graupel) was distributed (Emersic et al 2011). TFRs are well correlated with the graupel echo volume (Wiens et al 2005) and with updraft volume (>5 m s −1 ) above the >−5°C level (Deierling and Petersen 2008). Hence, the present results imply that both the volume and the magnitude of the updraft were enhanced effectively by vorticity growth in the mid-level MC, and that a large amount of graupel was produced above the freezing level.…”
Section: Mesocyclone (Mc) and Storm Developmentmentioning
confidence: 70%
“…Lightning intensity was closely linked with convection intensity. The strong updraft, a deep ice water mixing region, and large ice particles' flux may enhance lightning activities of a thunderstorm [6][7][8]. The intimate connection between electrical activity and some factors in the mixed-phase region was mainly due to the non-inductive charging process where rebounding collisions between big and small ice particles lead to appreciable charge separation.…”
Section: Introductionmentioning
confidence: 99%